Electronic medical record with Near Field Communication (NFC) authentication and telegram bot reminder / Muhammad Aizat Kamarudin - Kamarudin, Muhammad Aizat (Faculty of Computer and Mathematical Science, 2018)
Some of medical center still using manual method for recording and manage their record. This manual method works by writing the finalized of treatment have been done to the book or a sheet Manual record system is not efficient and brings more disadvantages to the doctor, patient and their clerk. Moreover, it also found that the manual record system has a high vulnerability of personal information stored on it. The findings that has been established has become the basis for the design and development aspect of this project. As this project’s aim to build a computerized record system, a Waterfall SDLC approach were used which includes six phases which are planning, analysing, design, development, testing and documentation. This project focuses on the NFC tag authentication with the off-line tag authentication technique while securing personal information stored in the database using Blowfish Encryption technique. Functionality testing has been done in order to test the system functionality and data security in these Electronic Medical Record System. Based on the testing result, it can be concluded that this project has successfully created Electronic Medical Record System prototype and improve the security of the data management in the Electronic Medical Record System. For future recommendation works, this project can be extended further by applying the encryption method to the patient record in order to protect the prevention of leak information inside that record. Lastly, added some features such as patient can receive their own record after finish the treatment for their own references in order to enhance the process understanding what the patient have or will been through. Based on the result of testing, the developed system is very helping clerk in the management of record compared to paper record system which is take a long time and hard to manage.